Semi‐Automatic Deposition of Oriented Cu(OH)2 Nanobelts for the Heteroepitaxial Growth of Metal–Organic Framework Films. Issue 21 (10th October 2021) - Linares‐Moreau, Mercedes; Brandner, Lea A.; Kamencek, Tomas; Klokic, Sumea; Carraro, Francesco; Okada, Kenji; Takahashi, Masahide; Zojer, Egbert; Doonan, Christian J.; Falcaro, Paolo
Abstract: Processing oriented metal–organic frameworks (MOFs) as thin films is a key challenge for their application to device fabrication. However, typical fabrication methods cannot generate precisely oriented crystals on commercially relevant scales (i.e., cm 2 ). This limits access to applications that require anisotropic functional properties (e.g., separation, optics, and electronics). Currently, highly oriented copper‐based MOFs are synthesized via the addition of the organic MOF component to an ethanolic solution of manually aligned Cu(OH)2 nanobelt films. In this work, the optimization of a semi‐automatic method for the fabrication of precisely oriented MOF films that affords a 100% yield of high quality ceramic films at the centimeter scale is reported. This improved fabrication protocol will facilitate the progress of heteroepitaxially grown MOFs for molecular separators and micro‐opto‐electronic devices. Abstract : Processing oriented metal–organic frameworks (MOFs) as thin films is a key challenge for their application to device fabrication. The deposition of highly oriented Cu(OH)2 nanobelt films is essential for the fabrication of precisely aligned copper‐based MOFs. Here, a semi‐automatic deposition method is introduced to obtain oriented and homogeneous Cu(OH)2 nanobelt films with a 100% yield at the cm scale.